Necesidad de reformar el art. 293 de la ley de propiedad intelectual, en relación a los derechos de una marca registrada y el registro de un nombre de dominio - Zambrano Matamoros, Guido Alexander (2017)
Due to technological advancement that has experienced the globalized world and hence our country in recent years, companies in order to advertise their products or services and marketing strategies to establish information and sell their products and have a presence at national and world have come to the need to create websites, which come true and real information of their products to consumers and the general public. Thus a natural or legal person is entitled to register a domain name to advertise their products through the Internet , System Domain Name Registration in Ecuador is responsible national organization called Nic Ecuador , a corporation nonprofit delegated by the "ICANN " (Internet Corporation of Assigned authority) , which means authorization World Corporation for Assigned Names Domain , these registers is performed in compliance with the requirements , the appropriate forms and payment to access to that name which is valid under the contract entitled to be renewed or transferred pursuant to the policies established by NIC- ECUADOR . The problem that we will analyze in this thesis, is the violation of intellectual property rights, the time domain names identical or similar to a trademark is registered, this infringement is based on two aspects that are: The first concerns the Organization Nic. Ecuador registers domain names without having the foresight to make a name search in the Intellectual Property Institute - IEPI - , in order to check if the domain name is different from a trademark, and thus protect the rights holders of registered trademarks or turn have an interconnection with the database - IEPI - to forewarn those rights, why conflicts between domains applicants and holders of trademarks arise therefore shock enters law trademark law in each country and to respect international treaties. And secondly when the names of the same domain are recorded trademarks may be taking advantage of the reputation and prestige of the brands based on effort and sacrifice have gained wide acceptance among consumers for their own characteristics, another factor is that these domain names would be inducing consumer deception about the products and services offered, all these criteria constitute acts of unfair competition, which are stipulated in the Law on Intellectual Property and the Law for the Regulation and Control of Power market . To try to avoid the existence of conflicts between users of domain names and trademark owners, where registered owners to claim their rights against a domain name that infringes the registered trademarks maraca empowering. The problem is based on the absence of national legislation to protect the rights of these warring group. Because one of them, users of domain names you can register in any country and would use worldwide, which does not happen with brands as their rights are limited to the country of registry so they are territorial rights. This implies the importance of today has all these problems in this thesis we intend to clarify these considerations by analyzing in detail the various conflicts appeared by using the domain name as the violation of the rights of intellectual property and formulate an exercise proposed to amend the Copyright Act and thus guarantee the rights established in the Constitution of the Republic of Ecuador.